(untitled) (Revista Contexto & Saúde, 2023)
The Family Health Strategy (ESF) has contributed as a fundamental basis for facing the Covid-19 pandemic. However, this scenario has subjected health professionals to routine changes and overload of activities, which may influence their satisfaction. Thus, the objective was to identify the factors that involve the satisfaction of ESF professionals in the time of the Covid-19 pandemic. This is a qualitative study, carried out from March to December 2020, with 64 health professionals. Semi-structured interviews and observation were carried out, submitted to thematic content analysis using the Atlas.ti 9.0 software. Regarding the factors that involve the satisfaction of professionals, three categories emerged: professional aspects (structure and materials available for assistance; organization of work and division of tasks in the team; professional resolution; and identification with the work); labor rights (stability in the employment relationship; remuneration; and workload); and professional recognition (professional recognition by management; and professional recognition by the user). It is concluded that the factors that involve the satisfaction of ESF professionals are linked to the work environment and its organization, to labor aspects and to recognition for the work developed, allowing greater security at this time of pandemic.